Pengaruh citra merek, kualitas produk dan harga terhadap minat beli pakaian anak-anak studi kasus toko Rizky dan Afdal Pariaman - Salfina, Lili; Gusri, Heza (Jurnal Indovisi, 2018)
This study aims to test empirically the influence of brand image, product quality and price on the interest of buying children's clothing in Rizky and Afdal stores partially and simultaneously. The type of this research is survey research and questionnaire. This research method is quantitative method. Population in this research is consumer or customer at store of Rizky and Afdal where the sample counted 100 responden. Data collection techniques were conducted with interviews and questionnaires. The research result showed that the brand image, product quality and price had positive effect on the buying interest of children's clothing in Rizky and Afdal shop partially and simultaneously.With multiple linear regression is Y = 0,226 0,137 0,712 0,119 and coefficient of determination give contribution equal to 93,9%. Given the positive relationship between brand image, product quality and price to buy children's clothing interest in Rizky and Afdal stores, it is expected to store Rizky and Afdal to increase sales revenue to always pay attention to things that attract consumer attention so that it can generate interest buy.